CONTENT MARKETING METRICS: THEORETICAL ASPECTS AND EMPIRICAL EVIDENCE - Rancati, Elisa; Gordini, Niccolo (European Scientific Journal, ESJ, 2014)
In recent years both practitioners and academics have shown an increasing interest in Content Marketing and in the metrics to measure its impact on firm performance. However the literature remains fragmented. In attempting to fill the gap, this paper has two main objectives. Firstly, we review the existing literature on content marketing and the main metrics used. Secondly, we analyse the degree of use and effectiveness of content marketing strategy and metrics, on a sample of 235 Italian firms.